The Implementation of Cipp Model in Evaluation MGMP Indonesian Language Program at Senior High School 11, Bekasi - Eka Septiani; Muchlas Suseno; Samsi Setiadi (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Program evaluation is a form of mechanism used to review program processes that have been implemented over a certain period of time. The review is intended to understand, explore, and correct deficiencies in the program itself. This study was evaluation research using the CIPP model (Context, Input, Process, Product) developed by Stufflebeam. The evaluation subjects were organizer of MGMP, instructors and principal in SMAN 11, Bekasi. The evaluation was conduted in SMAN 11, Bekasi. The data obtained are presented in descriptive qualitative form. Interview, observation, and documentation were utilized as instruments to collect the data. The results of this evaluation reveal that the dimensions of MGMP program planning are generally quite good in terms of the specified context aspect criteria. The dimensions of human resource capacity in implementating the MGMP program have not been optimal in running the program based on the specified input aspect criteria. The dimension of the implementation of the MGMP program have not met all the elements of the process aspect criteria. The dimension of achievement of the MGMP program in improving professionalism of Indonesian language teachers at SMAN 11, Bekasi have been achieved based on the success indicators that have been determined in product aspect.Keywords: MGMP, Program Evaluation, CIPP.